Potentially avoidable emergency department attendance: interview study of patients' reasons for attendance. Issue 12 (28th December 2011) - Agarwal, S; Banerjee, J; Baker, R; Conroy, S; Hsu, R; Rashid, A; Camosso-Stefinovic, J; Sinfield, P; Habiba, M
Abstract : Objectives: To explore the reasons for attendance at the emergency department (ED) by patients who could have been managed in an alternative service and the rate of acute admissions to one acute hospital. Design: Interview study. Setting: One acute hospital (University Hospitals of Leicester) in the East Midlands. Participants: 23 patients and/or their carers. Methods: A purposive sample of patients attending the ED and the linked urgent care centre was identified and recruited. Patients in the sample were approached by a clinician and a researcher and invited to take part in an interview. Patients of different ethnicities and from different age groups, arriving at the ED via different referral routes (self-referral, emergency ambulance, GP referral, out-of-hours services) and attending at different times of the day and night were included. The interviews were recorded and transcribed with the individuals' permission and analysed using the framework analysis approach. Results: Patients' anxiety or concern about the presenting problem, the range of services available to the ED and the perceived efficacy of these services, patients' perceptions of access to alternative services including general practice and lack of alternative pathways were factors that influenced the decision to use the ED. Conclusions: Access to general practice, anxiety about the presenting problem, awareness and perceptions of the efficacy of the services available in the ED and lack of alternative pathways are important predictors of attendance rates.